Caracterización morfológica en árboles nativos de guayaba en el valle del cauca (2005)
Se caracterizaron 53 accesiones de Psidium guajava, colectadas en 9 transectos del Valle del Cauca. En los descriptores cualitativos las accesiones se integraron en tres grupos que se diferenciaron por la forma del fruto. El 75% de los descriptores cuantitativos mostraron CV mayor al 24%. El 72.41% de la variación total de estos descriptores fue explicado en tres CP, que permitieron discriminar para variables de rendimiento del fruto, estructura del árbol y calidad del fruto. Abstract Morphological characteristics of guava in Cauca Valley, Colombia. 53 accesions were collected of Psidium guajava, in 9 transects of the Cauca Valley, these themselves were characterizates. In the descriptors qualitative the accesions were integrated in three groups that were differentiated for the form of the fruit. The 75% of the descriptors quantitative they showed greater VC to 24%. The 72.41% of the total variation of these descriptors, was explained in three PC, that permitted to discriminate for variables of performance of the fruit, structure of the tree and quality of the fruit. Keywords: Psidium guajava, accesions, descriptors quantitative, descriptors qualitative. Principal Component Analysis - PCA